Successful maternal and fetal outcome in patients with Takayasu arteritis: two case reports of Type I and Type IV in stage 2 - Upadhya, Rekha; Poojari, Vidyashree G.; Pai, Muralidhar V.; Nambiar, Jayaraman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Takayasu’s arteritis, is a rare, chronic, idiopathic, inflammatory disease of the large arteries, primarily involves the aorta, its main branches as well as the coronary and pulmonary arteries. It is mostly seen among women with child bearing age group (80%). During pregnancy, the increased intravascular volume impair circulation and exacerbate aortic regurgitation, hypertension, and congestive heart failure. Hypertension is one of the serious complication that can develop, leading to intrauterine growth restriction, maternal heart failure, and fetal haemorrhage and during postpartum period.